A GAMIFIED ESP-CALL FRAMEWORK FOR TECHNICAL VOCABULARY LEARNING IN VOCATIONAL COMPUTER NETWORK ENGINEERING: A QUASI-EXPERIMENTAL STUDY - Zubaidatul Hasanah; Khoirul Anwar (University of Kuningan, 2026)
This quasi-experimental study examined the effectiveness of a gamified English for Specific Purposes (ESP) Computer-Assisted Language Learning (CALL) framework for teaching technical vocabulary to vocational students in Computer Network Engineering. The study addressed two research questions: (1) To what extent does the gamified ESP-CALL framework improve students' technical vocabulary mastery? (2) What patterns of classroom engagement are observed during implementation? Forty eleventh-grade students from SMK Abdul Aziz Balung Jember, Indonesia, were assigned to experimental (n=20) and control (n=20) groups. The experimental group received four sessions of gamified instruction using Quizizz, Kahoot!, and simulation tasks with points, badges, timed missions, and team challenges. The control group received conventional textbook-based instruction. Pre-test and post-test vocabulary scores were analyzed using t-tests, ANCOVA, and Cohen's d effect size. Observation checklists measured visible engagement. Results showed the experimental group significantly outperformed the control group on post-test scores (M=77.70 vs 72.40; t(38)=2.80, p=.008). The effect size was large (Cohen's d=0.89). ANCOVA confirmed a significant group effect after controlling for pre-test scores (F(1,37)=28.91, p<.001, partial η²=.439). Observation data indicated higher visible engagement in the experimental group (average 3.66 vs 2.73). The findings suggest that integrating contextualized ESP content, multimodal CALL tools, and gamification elements can improve technical vocabulary learning in vocational EFL contexts. Limitations include short intervention duration (two weeks), single-site sampling, and imbalanced gender composition between groups.